Environmental Tax Reform: Eco-Friendly Policies in Indonesia Amid the Climate Crisis - Ocktarani, Ocktarani; Kasim, Elsie (UI Scholars Hub, 2024)
This research starts from the factual problem of the climate crisis phenomenon which causes a domino effect on the environment and the economic sector. Therefore, it is necessary to carry out environmental tax reform (green tax reform). Based on these problems, research was carried out to explain the green tax theory and look at green tax policy in Indonesia. The research method used in this research is qualitative with a constructivist approach. The result of the study indicate Indonesia's implementation of green tax rules signifies a proactive approach to addressing environmental challenges. However the effectiveness of these taxes is contingent upon resolving technical challenges. It is expected that the results of this research will provide new insights and recommendations for sustainable policies in the context of the environment and economy in Indonesia.